Consistent Value of Two-Stage Pedicle Flaps in the Age of Microsurgical Maxillofacial Reconstruction - Frohwitter, Gesche; Lutz, Rainer; Baran, Christoph; Weber, Margarete; Nobis, Christopher-Philipp; Rau, A.; Kesting, Marco Rainer (Journal of Maxillofacial and Oral Surgery, 2021)
Introduction: Up to the second half of the twentieth century, pedicled flaps marked the gold standard in reconstructive surgery. Followed by the introduction of microsurgical techniques, these flaps were increasingly abandoned. We conducted a retrospective study to determine the value of two-stage pedicle flaps in modern maxillofacial reconstruction. Material & Methods: A chart review from October 2017 to November 2020 was performed to identify patients who were treated by a two-stage pedicle flap in our Department of Oral and Maxillofacial Surgery. Results: A total of 31 patients, 17 female and 14 males received 36 two-stage pedicle flaps. All patients were in noticeably impaired health condition with a majority of ASA-score 3. The defect location mainly contained extraoral resections (58.3%). A variety of flaps were harvested consisting of buccal flaps, Abbe flaps, forehead flaps, deltopectoral flaps, nasolabial flaps, and a tubed flap. Discussion: The study outlines two indications for the use of two-stage pedicle flaps. Firstly, as a back-up strategy in heavily pre-treated wound beds and secondly in an almost contrarily indication as a first-choice reconstructive option of the facial skin in esthetic demanding cases. Conclusion: The timesaving and straight forward surgical approach as well as their low postsurgical complications and strong long-time success rates secure the two-stage pedicle flap a justified niche role in times of microsurgical maxillofacial reconstruction.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Back-up procedures; Pedicle flaps; Reconstructive surgery; Transplant autonomy